2015
DOI: 10.1515/bvip-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Synovial Fluid Inflammatory Mediators and Cartilage Biomarkers After Experimental Acute Equine Synovitis

Abstract: The purpose of the study was to define transient changes in the concentration of inflammatory biomarkers and cartilage biomarkers in the synovial fluid of joints following experimentally induced acute equine synovitis. Acute synovitis was induced in eight skeletally mature mares by a sterile intra-articular injection of 1 mL of phosphate-buffered saline (PBS) containing 0.5 ng of lipopolysaccharide (LPS). The solution was injected into the right middle carpal joint. One mL of sterile PBS was injected into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The study illustrated that in the model group horses it increased sharply after the second week compared with the control group. A significant increase in CTX-II concentration occurred before significant lameness, which was consistent with the previous research ( 28 ). The degradation of type II collagen occurred late, which may be related to the time of action of MMP-13 and the complex helical structure of type II collagen.…”
Section: Discussionsupporting
confidence: 92%
“…The study illustrated that in the model group horses it increased sharply after the second week compared with the control group. A significant increase in CTX-II concentration occurred before significant lameness, which was consistent with the previous research ( 28 ). The degradation of type II collagen occurred late, which may be related to the time of action of MMP-13 and the complex helical structure of type II collagen.…”
Section: Discussionsupporting
confidence: 92%
“…For the other doses, joint effusion and cellularity of the synovial fluid were observed, compatible with synovitis and accounting for the presence of pain in some animals. After contact with a joint, LPS triggers marked increases in synovial leukocytes and total protein concentration, in addition to inflammatory biomarkers such as prostaglandin E2, interleukin 1β, and TNF, with a peak occurring as long as 8 h after inoculation and a return to the baseline after 168 h. 31 The changes in our sheep were observed as long as 48 h after LPS administration in phase 1.…”
Section: Discussionmentioning
confidence: 51%
“…However, comparing our results to those of a previous study where increases in markers of inflammation-synovial white blood cell counts and total protein-were seen in saline injected control joints [49], it is clear that those increases were substantially less than the increases noted here. Other studies have reported that significantly greater increases were seen in a number of synovial biomarkers, such as prostaglandin E2 and tumor necrosis factor-alpha, in LPS-injected joints compared to joints injected with a negative control (saline) [28,50]. Considering this clear evidence from earlier reports and the overarching aim to respect the principles of 3 R and reduce the number of animals used, we could not justify adding additional animals as controls.…”
Section: Discussionmentioning
confidence: 95%